2020
DOI: 10.1007/s13300-020-00888-w
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Role of Renal Biopsy in Patients with T2DM: A Literature Review of Global Renal Biopsy Results

Abstract: Introduction Renal biopsy performed in patients with type 2 diabetes mellitus (T2DM) for atypical or suspected diabetic kidney disease (DKD) reveals one of three possibilities: diabetic nephropathy (DN, pathological diagnosis of DKD), nondiabetic kidney disease (NDKD) and DN plus NDKD (mixed form). NDKD (including the mixed form) is increasingly being recognized worldwide. With the emerging concept of DKD and the complexity of routine application of renal biopsy, the identification of “clinical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 84 publications
2
41
0
1
Order By: Relevance
“…Tong et al have searched identified 40 studies worldwide between 1977 and 2019 that looked at global renal biopsy and pathological nondiabetic kidney disease (NDKD) lesions. The results have shown that overall prevalence rate of DN, NDKD and DN plus NDKD is 41.3, 40.6 and 18.1%, respectively (13). Therefore, it is of great significance to do renal biopsy as early as possible to confirm the diagnosis and to enable personalized treatment especially when T2DM patients present atypical diabetic kidney disease (DKD) symptoms (e.g., absence of diabetic retinopathy, shorter duration of diabetes, microscopic hematuria, subnephrotic range proteinuria, lower glycated hemoglobin, lower fasting blood glucose).…”
Section: Diabetic Nephropathy (Dn)mentioning
confidence: 93%
“…Tong et al have searched identified 40 studies worldwide between 1977 and 2019 that looked at global renal biopsy and pathological nondiabetic kidney disease (NDKD) lesions. The results have shown that overall prevalence rate of DN, NDKD and DN plus NDKD is 41.3, 40.6 and 18.1%, respectively (13). Therefore, it is of great significance to do renal biopsy as early as possible to confirm the diagnosis and to enable personalized treatment especially when T2DM patients present atypical diabetic kidney disease (DKD) symptoms (e.g., absence of diabetic retinopathy, shorter duration of diabetes, microscopic hematuria, subnephrotic range proteinuria, lower glycated hemoglobin, lower fasting blood glucose).…”
Section: Diabetic Nephropathy (Dn)mentioning
confidence: 93%
“…Type 2 diabetes patients are often older at the time of diagnosis and kidney disease due to other causes than diabetes is likely to occur. Several studies have verified that kidney disease in type 2 diabetes may be a more compounded entity than what is seen in type 1 diabetes ( 9 ). One study from the United States which examined kidney biopsies in patients with type 2 diabetes and kidney disease found that typical diabetic microvascular disease were present in 37% of the cases, non-diabetic kidney disease in 36% of the cases, such as nephrosclerosis or immunological kidney disease, while mixed forms of diabetic and non-diabetic kidney disease were found in 27% of the cases ( 10 ).…”
Section: Kidney Disease In Patients With Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…increased albuminuria, hypertension and slow decrease in estimated GFR). However, other diseases must be suspected when no other microvascular complications of diabetes are present and also in the presence of microscopic haematuria ( 9 ). The pathological classification system developed for chronic kidney disease in type 1 diabetes also includes type 2 diabetes ( 3 ).…”
Section: How To Diagnose Kidney Disease In Patients With Diabetes?mentioning
confidence: 99%
“…Diabetic nephropathy (DN) is one of the most common complications of Diabetic Mellitus (DM) (1). Parallel with the rising global prevalence of diabetes, DN often occurs after diabetic retinopathy, another microvascular complication of DM, presenting symptoms after 10 to 15 years of diabetes (2)(3)(4). The characteristics of DN are concluded as persistent proteinuria, reduced total glomerular filtration rate, raised arterial blood pressure, fluid retention, and shrunken kidney size (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%